Magnus effect for roll-decoupled canards on a spinning body of revolution. Issue 2 (14th May 2020) - Klatt, Daniel; Mielke, Alina; Mundt, Christian
Abstract : Purpose: Spinning slender bodies are affected by lateral Magnus forces and moments when exposed to cross-flow. The effects occurring for spinning bodies of revolution in combination with stabilising or control surfaces such as canards are not yet fully explained. Therefore the present work aims to investigate the phenomena arising from the interactions of a roll-decoupled guidance unit with a spinning rear body are investigated. Design/methodology/approach: A generic tangential-ogive-cylinder projectile equipped with deflectable canards on a roll-decoupled nose is investigated by means of 3D Reynolds-averaged Navier–Stokes simulations at Mach number 2 for angles of attack up to 22 degrees. Different canard deflection angles up to 9 degrees are considered. Global aerodynamic coefficients as well as local flow fields are analysed to explain the interactions occurring between the roll-decoupled guidance unit and the spinning rear body. Findings: The deflected canards lead to flow interactions resulting in lateral forces and moments even without a spinning motion of the rear part. Depending on the canard deflection angles, these forces act in or against the direction of the classical Magnus effect. For angles of attack smaller than 10 degrees it is possible for the current body geometry to directly superpose the lateral effects resulting from the fins for the non-spinning model with those occurring for the non-finned but spinning model to obtain the total forces and moments acting on a spinning model with canted canards. However, the lateral effects generated on the guidance unit itself are insignificant compared to the canard-induced effects on the rear body. Originality/value: A detailed analysis of the interaction effects arising from a decoupled guidance unit containing canards with a non-spinning/spinning rear body is performed and the underlying phenomena are revealed.